2016
DOI: 10.1016/j.immuni.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing Microbiota-Induced Retinoic Acid Deficiency Stimulates Protective CD8 + T Cell-Mediated Immunity in Colorectal Cancer

Abstract: Summary Although all-trans retinoic acid (atRA) is a key regulator of intestinal immunity, its role in colorectal cancer (CRC) is unknown. We found that mice with colitis-associated CRC had a marked deficiency in colonic atRA due to alterations in atRA metabolism mediated by microbiota-induced intestinal inflammation. Human ulcerative colitis (UC), UC-associated CRC, and sporadic CRC specimens have similar alterations in atRA metabolic enzymes, consistent with reduced colonic atRA. Inhibition of atRA signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 47 publications
7
115
0
Order By: Relevance
“…In human sporadic CRC, UC and UC-associated CRC, the atRNA-synthesizing enzyme ALDH1 is significantly decreased whereas the atRNA-catabolizing enzyme CYP26A1 is increased, suggestive of common atRA deficiency in these pathologies (31*). Using the AOM/DSS CAC mouse model, Bhattacharya et al demonstrated that atRA protects against tumorigenesis by enhancing anti-tumor CD8+ T cell response and that microbiota-induced inflammatory cytokines promote differential expression of ALDH1 and CYP26A1 as observed in patients (31*). The microbiota metabolite butyrate was recently shown to stimulate ALDH1 expression, thereby increasing atRA levels in epithelial cells (32).…”
Section: Metabolismmentioning
confidence: 99%
“…In human sporadic CRC, UC and UC-associated CRC, the atRNA-synthesizing enzyme ALDH1 is significantly decreased whereas the atRNA-catabolizing enzyme CYP26A1 is increased, suggestive of common atRA deficiency in these pathologies (31*). Using the AOM/DSS CAC mouse model, Bhattacharya et al demonstrated that atRA protects against tumorigenesis by enhancing anti-tumor CD8+ T cell response and that microbiota-induced inflammatory cytokines promote differential expression of ALDH1 and CYP26A1 as observed in patients (31*). The microbiota metabolite butyrate was recently shown to stimulate ALDH1 expression, thereby increasing atRA levels in epithelial cells (32).…”
Section: Metabolismmentioning
confidence: 99%
“…Researchers finally illustrated that pretreatment with broad-spectrum antibiotics, which deplete the whole microbiota, completely prevents all-trans-retinoic acids in this mouse model. Interestingly, human colon cancer specimens have also shown deficiency in all-trans-retinoic acid, similar to the animal model (46). Nevertheless, further investigation is required to determine if this deficiency in human colon cancer is related to microbiome and whether it can be reversed by all-trans-retinoic acid supplementation towards a better immune response and prognosis.…”
Section: Microbiota In Favor Of Tumorigenesis Through T Cellsmentioning
confidence: 81%
“…Depletion of all gut microorganisms by broad-spectrum antibiotics in animal models predisposed to colon cancer is another example of experiments, analyzing the association between whole microbiota and colon cancer. In general, antibiotic treatment of mice significantly decreases tumor formation and progression (46,47). There are studies on colon cancer linking a single bacterium, e.g.…”
Section: Microbiota In Favor Of Tumorigenesismentioning
confidence: 99%
See 2 more Smart Citations